TINGKAT KESEHATAN MENTAL GENERASI Z KOTA MAGELANG BERDASARKAN INTENSITAS PENGGUNAAN MEDIA SOSIAL - Zidan Rizka Alhafidz (Universitas Muria Kudus, 2025)
This study aims to describe the mental health status of Generation Z in Magelang City based on the intensity of social media use. The research method used was quantitative descriptive with 50 respondents aged 15-24 years selected through purposive sampling. The research instruments included a questionnaire on the intensity of social media use and a mental health questionnaire. The data were analysed using frequency distribution and percentages. The results showed that 46% of respondents used social media for more than 4 hours per day, with Instagram and TikTok as the dominant platforms. Mental health conditions showed that 46% of respondents were in the poor category, 44% experienced high anxiety, and 40% had low positive emotions. There was a pattern of tendency that the higher the intensity of social media use, the worse the mental health condition of the respondents. The study recommended comprehensive interventions through digital literacy programmes, counselling services, and policies that support the psychological well-being of Generation Z.